Caractérisation sur estran des performances de croissance, maturation et survie des deux-taxons d'huîtres creuses C. gigas et C. angulata, hybrides et "exotiques" - Soletchnik, Patrick; Huvet, Arnaud; Le Moine, Olivier; Razet, Daniel; Geairon, Philippe; Goulletquer, Philippe; Faury, Nicole (Présentation Journées Conchylicoles, Ifremer Nantes, 3-4 avril 2001, 2001)
This study presents the zootechnical performances in their natural habitat, the Marennes Oléron Bay, of two Crassostrea gigas and Crassostrea angulata taxons of European and Asian origin, as well as those of their "European" hybrids (6 studied strains). Growth performance seems to be a phenotypic characterisation linked with the maternal origin (c. gigas or C. angulata). The Asian "pure gigas" or "pure angulata" strains' growth performances differ more from those of their European "sisters" than the European taxons with their hybrids. The C. angulata strain, of Taiwanese origin, does not survive the second culture week in the Marennes Oléron Bay. The C. angulata strain seems to "carry" a strong mortality potential. After 6 months of off-bottom culture, the mortality rate for C. angulata and the two hybrids is comprised between 25 and 35 %, whereas that of the two C. gigas strains, of Japanese origin or acclimated to the Marennes Oléron Bay, is only 15-25 %. By the end of 2000, the culture performance is only + 5% from the hybrid of C. angulata mother. The best performance is obtained by Crassostrea gigas from the Marennes Oléron Bay, with +22%. The 3 other strains have a performance of about + 10-13 %. Growth and survival results show that C. gigas is superior to the others in its environment and suggests its local adaptation. From an application point of view, the hybrids' "average" performances demonstrate their limited capacity in diversifying French oyster culture. Cette étude présente les performances zootechniques en milieu naturel, dans le Bassin de Marennes Oléron, des deux taxons Crassostrea gigas et Crassostrea angulata d'origine européenne et asiatique, et de leurs hybrides "européens" (6 souches étudiées). La performance de croissance semble être une caractérisation phénotypique liée à l'origine maternelle (c. gigas ou C. angulata). Les souches asiatiques "pures gigas" ou "pures angulata", s'éloignent plus des performances de croissance de leurs "soeurs" européennes que les taxons européens avec ...